Evolution of asylum policies of the German government during the refugee crisis in 2015 - Kirmová, Kamila Ece; Votoupalová, Markéta; Kristek, Tomáš; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2023)
The bachelor thesis focuses on the changes in asylum policy in Germany during the European migration crisis between the years 2014-2016. The research question it answers is whether Germany’s asylum policy changed during the crisis, and if so, how and under which circumstances. The thesis is built on general theoretical approaches to asylum policy derived from conceptualized theories of international relations. The research follows Germany and its applied measures in the form of a legislative discourse. It is a case study analytically researched using mainly qualitative secondary data. The thesis is also enriched by quantitative data in the form of statistics of refugees entering the country. The research brings valuable information in the form of an intertwinement of the theoretical approaches to asylum policy with the German realities of implemented measures and legislation. The findings indicate that Germany’s asylum policy did, in fact, change, but only for a shorter period due to Angela Merkel’s liberal approach and her Wilkommenskuktur open-door policy. The asylum policy later changed back to its restrictive roots, with the realist and national identity approach having overruled the liberal one.
Vedoucí práce: Markéta Votoupalová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: mezinárodní studia - diplomacie [obor bakal. práce]; bakalářské práce; bachelor's theses